2019
DOI: 10.3389/fmicb.2019.01770
|View full text |Cite|
|
Sign up to set email alerts
|

Gut Microbiota as an Objective Measurement for Auxiliary Diagnosis of Insomnia Disorder

Abstract: Insomnia is a type of sleep disorder which is associated with various diseases’ development and progression, such as obesity, type II diabetes and cardiovascular diseases. Recent investigation of the gut-brain axis enhances our understanding of the role of the gut microbiota in brain-related diseases. However, whether the gut microbiota is associated with insomnia remains unknown. In the present investigation, leveraging the 16S rDNA amplicon sequencing of V3-V4 region and the novel bioinformatic analysis, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 71 publications
3
52
2
Order By: Relevance
“…Although IL-6 did not change signi cantly in insomnia patients, we still found a correlation between IL-6 and gut bacteria, which is different from the results of Smith et al Bacteroides have been shown to increase signi cantly in the intestines of patients with insomnia 21 . It plays an important role in the gut microbiome and can be used as an important biomarker for identifying insomnia patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although IL-6 did not change signi cantly in insomnia patients, we still found a correlation between IL-6 and gut bacteria, which is different from the results of Smith et al Bacteroides have been shown to increase signi cantly in the intestines of patients with insomnia 21 . It plays an important role in the gut microbiome and can be used as an important biomarker for identifying insomnia patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The shift in populations of gut microbiota has been associated with various diseases, in this study, we demonstrated that α-and β-diversity of the gut microbiota in insomnia patients is signi cantly altered, which is similar to the result of Liu et al 21 . We found primarily the beta diversity of the gut microbiota in insomniacs is different, alpha diversity rarely varied.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Random forest together with cross-validation identified two signature bacteria, which could be used to distinguish insomnia patients from the healthy population (Bactecteroides; Clostridiales). The gut flora interaction networks were significantly altered for patients with insomnia compared with the control group [81]. Smith et al used actigraphy to quantify sleep measures coupled with gut microbiome sampling to determine how the gut microbiome correlates with various measures of sleep physiology.…”
Section: Gut Microbiome Diversity Is Associated With Sleep Physiologymentioning
confidence: 99%
“…The gut microbiota, despite its complexity and great variation between individuals, was shown to be predictive of various intestinal diseases and conditions, such as irritable bowel syndrome (IBS) [ 3 ], Crohn’s disease [ 4 , 5 ], and colorectal cancer [ 6 ]. Interestingly, the composition of the gut microbiome also predicts some non-intestinal illnesses, such as coronary artery disease [ 7 ], liver fibrosis [ 8 ], metabolic diseases/obesity [ 9 ], insomnia [ 10 ], and bipolar depression [ 11 ]. Another classification setting is the detection of contamination in samples.…”
Section: Introductionmentioning
confidence: 99%